Psychometric Analysis of the Dating Anxiety Scale for Adolescents in Samples of Polish and U.S. Young Adults: Examining the Factor Structure, Measurement Invariance, Item Functioning, and Convergent Validity. (December 2022) - Adamczyk, Katarzyna; Morelli, Nicholas M.; Segrin, Chris; Jiao, Jian; Park, Jung Yeon; Villodas, Miguel T.
This study explored whether the Dating Anxiety Scale for Adolescents (DAS-A), which was originally developed in the United States to assess dating anxiety in adolescents, is appropriate for use in samples of young adults from Poland and the United States. The factor structure, measurement invariance across country, gender and relationship status, degree of precision across latent levels of the DAS and the functioning of individual items, and convergent validity were examined in a sample of 309 Polish and 405 U.S. young adults. The confirmatory factor analysis (CFA) supported the original three-factor measurement model of the DAS. Invariance tests revealed factor loadings and item thresholds that differed across subgroups, supporting partial metric and partial scalar invariance. The MIRT analysis showed that all items adequately discriminated participants with low and high anxiety. Dating anxiety latent factor correlations with mental health and interpersonal competence were significant in the expected negative directions. The results call for careful interpretation of research involving the DAS in cultural, gender, and relationship status groups, particularly when the primary goal is to compare mean levels of dating anxiety. Further development of the scale is recommended before it can be used across country, gender, and relationship status groups.